Influência da configuração superficial dos diferentes tratamentos de superfície e de sistemas adesivos na resistência adesiva de pinos de fibras de vidro: estudo in vitro - Fernando Molinari Gomes Gilson (2006)
The Idea of using root canals as retention places in endodontically treated teeth is not new. The post Ls function is to provide retention and support to restorative materials. Adhesive cementation of glass fiber posts and the consequent core build up of a weakened tooth is a critical procedure, because of the several concerns involved and the great amount of materials available on the market and its different protocol instructions. This study evaluated the influence of different post configurations, post surface treatments and adhesive systems on retention of glass fiber posts on artificial root canals made of composite resin. The dual cure adhesive Excite DSC Soft Touch EndoR and the chemically activated adhesive LOKR were tested. Silane coupling agent and sandblasting with alumina oxide at 50Êm were the different surface treatments tested. The different post configurations were serrated posts or smooth posts. After cementation, the specimen were stored in distilled water at 37 C for 5 days and then submitted to push-out tests. Also the type of failure was recorded. The adhesive Excite DSC Soft Touch EndoR was the most retentive. And, after microscopical observation it was concluded that sandblasting and serrated posts exhibited better performance than silane coupling agent on retention of the posts.